Aplikasi Administrasi Kependudukan Di Kecamatan Prabumulih Selatan Berbasis Web - Putri, Enisa; Khana Wijaya; Fajriyah Fajriyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
South Prabumulih Prabumulih City is one of the government institutions located under the auspices of the Prabumulih City Government. The method of managing population burden at this institution still uses manual plants which causes frequent errors resulting in inaccurate data. The aim of this research is to build a user application using the District Office is obliged to process population administration data using research methods using descriptive qualitative methods with data collection techniques in the form of observation interviews and library studies device development methods using the Waterfall method in terms of system design used by users class diagrams diagrams and building activities using websites with language XL programming and print reports using the PDF document format